2023
DOI: 10.1146/annurev-fluid-032822-125417
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Liquid Foam Dynamics: From Structural Elements to Continuum Descriptions

Abstract: Gas-liquid foams are important in applications ranging from oil recovery and mineral flotation to food science and microfluidics. Beyond their practical use, they represent an intriguing prototype of a soft material with a complex, viscoelastic rheological response. Crucially, foams allow detailed access to fluid-dynamical processes on the mesoscale of bubbles underlying the large-scale material behavior. This review emphasizes the importance of the geometry and interaction of mesoscale structural elements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Yanagisawa et al reported that a liquid film of foam bubble bursts with a velocity greater than 20 m/s 44 . In addition, finer, needle like fractures at the fingertips signal the onset of film ruptures in a radial Hele-Shaw cell 20 . In this study, the fingertip velocities are 0.5 m/s at 4.0 psi and 3.2 m/s at 10.0 psi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yanagisawa et al reported that a liquid film of foam bubble bursts with a velocity greater than 20 m/s 44 . In addition, finer, needle like fractures at the fingertips signal the onset of film ruptures in a radial Hele-Shaw cell 20 . In this study, the fingertip velocities are 0.5 m/s at 4.0 psi and 3.2 m/s at 10.0 psi.…”
Section: Resultsmentioning
confidence: 99%
“…There are a few studies on the displacement of liquid foam by gas in a Hele-Shaw cell. Injecting gas at a continuous flow rate or constant pressure into a body of liquid foam in a Hele-Shaw cell leads to finger-like gas/foam interfaces 20 . This behavior is the well-known Saffman-Taylor instability because viscous foam is pushed by a less viscous gas in a porous medium 2 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…As has been mentioned, various components can be included in models for foam structures (bubbles, films, vertices, Plateau borders and such like [50]). In the viscous froth model, however, the basic structural unit is an element of foam film [36].…”
Section: (A) Viscous Froth Governing Equationmentioning
confidence: 99%
“…The staircase structures studied here are comprised [50] of the bubbles themselves, films between bubbles and also vertices at which three films meet. The foam is considered to be dry, so films can be treated as one-dimensional lines (or more generally curves) and vertices can be treated as points.…”
Section: Background and Novel Contributionmentioning
confidence: 99%